On the three-terminal interactive lossy source coding problem - Rey Vega, Leonardo; Piantanida, Pablo; Hero, Alfred O. (Proceedings / IEEE International Symposium on Information Theory, 2014)
The three-node multiterminal lossy source coding problem is investigated. We derive an inner bound to the general rate-distortion region of this problem which appears to be the natural extension of the seminal work by Kaspi [1] on the interactive two-terminal source coding problem. It is shown that this -rather involved- inner bound contains several rate-distortion regions of some relevant source coding settings. In this way, besides the non-trivial extension of the interactive two terminal problem, our results can be seen as a generalization and hence unification of several previous works in the field.